Improving Human Rights A Conversation with Emilie Hafner-Burton. - Burton, Howard (Ideas Roadshow Conversations Ser., 2020)
This book is based on an in-depth, filmed conversation between Howard Burton and Emilie Hafner-Burton, the John D. and Catherine T. MacArthur Professor of International Justice and Human Rights at UC San Diego and co-director of the Laboratory on International Law and Regulation at the School. This extensive conversation covers topics such international law, when and why international laws work and don't work, the international human rights system and concrete measures that could be taken to improve it, the International Criminal Court, and the role of states in the protection of human rights.